P5460Prevalence of left atrial enlargement in patients undergoing an echocardiogram for cardiovascular risk stratification at an esh excellence centre in italy - Muiesan, M L; Salvetti, M; Paini, A; Aggiusti, C; Bertacchini, F; Stassaldi, D; Capellini, S; Casella, E; Arnoldi, C; Agabiti Rosei, E (European heart journal, 2019)
Abstract Background Left atrial (LA) enlargement (LAE) is associated to an increased risk of cardiovascular complications, and in particular of atrial fibrillation. The 2018 ESH/ESC Hypertension guidelines suggested the use of LA volume instead of linear dimensions, and for the first time proposed the indexation to height2 (h2) The aim of our study was to assess the prevalence of left atrial dilatation in a large sample of patients undergoing an echocardiogram for cardiovascular risk stratification at an ESH excellence centre in Italy. Design and methods 3872 subjects undergoing a diagnostic work-up for arterial hypertension (known or suspect) were analysed. The mean age was 56±15 years, BMI 26±5 kg/m, 44% normal weight, 39% overweight, 17% obese, 53% males. Left atrial volume was measured by the area-length method using the apical 4-chamber and 2-chamber views. Results The prevalence of left ventricular hypertrophy (LVH) was 11% when indexing for BSA and 12% when indexing for height2.7. LAE was observed in 30% of subjects when indexing for h2 and in 9% when indexing for BSA. In obese or overweight subjects the prevalence of LAE was 38% of subjects when indexing for h2 and in 11% when indexing for BSA. The different prevalence of LAE was particularly evident in extremely obese patients. LAE was very common in patients with LVH: 62% and 26% when indexing for h2 and for BSA, respectively. Interestingly, it was frequent also in patients without LVH, in particular when the indexation for h2 was used (25% as compared to 7% when indexing for BSA). Conclusions In a large sample of subjects undergoing a diagnostic work-up for arterial hypertension LAE was frequently observed, particularly when the new indexation proposed by the 2018 ESH/ESC hypertension guidelines was used. Even in the absence of clear-cut LVH, LAE was observed in one quarter of subjects. The indexation to BSA leads to an under-recognition of LAE, in particular in patients with overweight and/or obesity